The bone readers science and politics in human origins research - Tuniz, C. (Claudio); Gillespie, Richard; Jones, Cheryl (Left Coast Press, 2009)
"Who owns the past? Scientists are reconstructing human prehistory with ever more refined techniques at a time when Indigenous people are demanding ownership of it, and when many archaeologists are challenging the primacy of scientific evidence. 'The bone readers' examines the most controversial issues in Australian pre-history. With a razor sharp eye and a fine sense of irony, the authors explain which hypotheses don't have legs and expose the implications for the politics of the present. They examine the facts and myths about first human arrival in Australia and later waves of arrivals, the implications of the discovery of Homo floresiensis (hobbits), sensitivities around the demise of megafauna, rock art dating, and what DNA tells us about ownership of human remains. Findings in Australia have implications for the history of the human species throughout the world, and they show how they can throw light on human lineages and animal extinctions elsewhere. Throughout they explain the complexities of scientific techniques for the general reader. This book sets the record straight for readers puzzled by the myriad claims and counterclaims. Not shy of controversy, it is bound to stir debate."--Provided by publisher